2022
DOI: 10.1007/s40429-022-00437-4
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Disorder and Stigma: Opportunities for Treatment and Prevention

Abstract: Purpose of Review Gambling disorder is among the most stigmatized mental health problems. More research is needed to understand the mechanisms that underlie this stigma and the effects of stigma-reduction interventions. This paper reviews extant literature on the stigma of gambling disorder and highlights evidence from this research and the broader mental illness stigma literature to help advance research on the prevention and reduction of gambling-related stigma. Recent Finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Ethical consideration : GD is associated with stigmatization ( Palmer, Richardson, Heesacker, & DePue, 2018 ), and women might be more prone to experience stigmatization ( Dąbrowska & Wieczorek, 2020 , 2021 ; Quigley, 2022 ) being in the minority among those with GD. Further, experiences of suicidality can be a sensitive subject that can evoke thoughts and emotions that need immediate attention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical consideration : GD is associated with stigmatization ( Palmer, Richardson, Heesacker, & DePue, 2018 ), and women might be more prone to experience stigmatization ( Dąbrowska & Wieczorek, 2020 , 2021 ; Quigley, 2022 ) being in the minority among those with GD. Further, experiences of suicidality can be a sensitive subject that can evoke thoughts and emotions that need immediate attention.…”
Section: Methodsmentioning
confidence: 99%
“…An Australian study examining why young women tend to gamble more frequently than previously found that feminization of commercials, gambling as a family activity – often with their fathers, and gambling as a social event might explain this increase ( McCarthy, Thomas, Pitt, Daube, & Cassidy, 2020 ). Despite this feminization, women with GD often experience stigmatization ( Dąbrowska & Wieczorek, 2020 , 2021 ; Quigley, 2022 ). This fear of stigmatization also appears to be a barrier to seeking treatment ( Dąbrowska & Wieczorek, 2020 , 2021 ), and might affect suicidality.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of mental illness among healthcare workers is a major concern, and it can lead to exhaustion, burnout, and impaired job performance (Vroege & Broek, 2022). Moreover, negative and stigmatizing beliefs about people with mental illness are prevalent among healthcare professionals, which can further exacerbate the challenges faced by individuals with mental health issues (Quigley, 2022).…”
Section: Overview Of Mental Health In Healthcare Settingsmentioning
confidence: 99%
“…Hasil lainnya melaporkan terdapat korelasi antara perilaku judi remaja dan dampak psikologis, sosial dan ekonomi (Livazović dan Bojčić, 2019). Saat ini perilaku perjudian menjadi masalah Kesehatan mental yang paling distigmatisasi (Quigley, 2022). Stigma masih menjadi permasalahan yang dirumuskan dalam pencegahannya (Putri dan Tania, 2021;Tania et al, 2021).…”
Section: Pendahuluanunclassified